Pengaruh Citra Negara, Citra Merek, Dan Negara Asal Terhadap Minat Beli Pada Smartphone Di Indonesia - Muhammad Imam Al Gibran dan Chairy (Jurnal Manajemen Bisnis dan Kewirausahaan, 2019)
Smartphone is all about its specification, the more powerful your smartphone is, more expensive it can be. Yet later, China offers a lot of variations with high specification, but also with a cheap price. Smartphone from China is often called ‘scam’ or ‘will be broken easily’, or even ‘not durable’. In this research I want to know either Country Image, Country of Origin, and Brand Image will affect the Purchase Intention or not. It’s not that clear because some people still buy the smartphone made in China.